EKSISTENSI PEMBELAJARAN JARAK JAUH PAI DAN LAYANAN BK ISLAMI ONLINE DI SMP KABUPATEN SIDOARJO - Eni Fariyatul Fahyuni (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
This study aims to examine the existence of distance learning Islamic religious education and online guidance and counselling services during the Covid-19 pandemic and to find out the opportunities and challenges in implementing distance learning and online Islamic counselling services at SMP Sidoarjo Regency during the COVID-19 pandemic. This research uses qualitative research methods that are careful, thorough, and careful about a program that implemented, various events and activities carried out both as a whole and individually. Data collection techniques in this study use interviews and observation. Researchers conducted interviews to collect information related to distance learning in several subjects that were applied through the PAI distance learning system and online BK services implemented at SMP Sidoarjo Regency by interviewing them directly. For the observation phase, researchers implemented PAI distance learning and online BK services carried out by junior high schools in the Sidoarjo Regency. Challenges and opportunities for implementing distance PAI learning and online guidance and counselling services during the COVID-19 pandemic, creating a platform with features for distance PAI learning and online guidance and counselling services that accommodate increased self-efficacy and achievement motivation.